ANALISIS PROFITABILITAS USAHATANI BAWANG MERAH BERDASARKAN MUSIM DI TIGA KABUPATEN SENTRA PRODUKSI DI INDONESIA - Haris F. Aldila; Anna Fariyanti; Netti Tinaprilla (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
The  objectives  of  this  research  are  (1)  to  analyze  the  characteristics  of farmers  and the  performance  of shallot  farming and  (2) to  analyze the profitability of shallot  farming  in  production  centers  in  Java.  The  research  was  conducted  in Cirebon,  Brebes,  and  Tegal  regency  with  the  number  of  respondents  each  of  40 farmers. Farm profitability level indicated by R/C ratio in every season (rainy season, first  dry  season  and  second  dry  season)  during  2013/2014.  The results  showed  that shallot  farming in Cirebon, Brebes, and Tegal feasible and profitable  to cultivate in every season. Farmers in Cirebon had the biggest gain in the second dry season of Rp 47 million per hectare with R/C of 1.65. Farmers in Brebes had the biggest gain in the first  dry season amounted to Rp 23 million per hectare with R/C of 1.42. Farmers in Tegal had the biggest gain in the rainy season of Rp 31 million per hectare with R/C of 1.48.